2013
DOI: 10.2478/jppr-2013-0046
|View full text |Cite
|
Sign up to set email alerts
|

First Notice of Phytophthora Crown and Root Rot of Euphorbia Pulcherrima in Polish Greenhouses

Abstract: The plant pathogen, Phytophthora cryptogea, was recovered from 4/5 of the 75 poinsettias collected from two greenhouse farms. The poinsettias showed stunting and wilting as well as stem base and root rot symptoms. Representative isolates of the species from two poinsettia cultivars, colonized stem parts, leaf petioles, leaf blades and root parts. Stem parts of 6 cultivars were colonized at a slower rate than other poinsettia organs. Isolate from Euphorbia pulcherrima also colonized stem parts and leaf blades o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Previous studies showed that the infection rate of F. oxysporum was relatively slow. For example, F. oxysporum can infect Lilium (Zhang et al 2018), Cymbidium ensifolium (Yao et al 2018), Cyclamen (Kim et al 2003), Euphorbia pulcherrima (Orlikowski and Ptaszek 2013), Chrysanthemum (Singh and Kumar 2011), Eustoma grandiflorum (Li et al 2010), and Dianthus caryophyllus (Ardila et al 2011). These hosts are herbaceous plants, and it takes at least 30 d or even 2-3 months from infection to plant death.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the infection rate of F. oxysporum was relatively slow. For example, F. oxysporum can infect Lilium (Zhang et al 2018), Cymbidium ensifolium (Yao et al 2018), Cyclamen (Kim et al 2003), Euphorbia pulcherrima (Orlikowski and Ptaszek 2013), Chrysanthemum (Singh and Kumar 2011), Eustoma grandiflorum (Li et al 2010), and Dianthus caryophyllus (Ardila et al 2011). These hosts are herbaceous plants, and it takes at least 30 d or even 2-3 months from infection to plant death.…”
Section: Discussionmentioning
confidence: 99%
“…Three species of Phytophthora have been reported from poinsettia: P. drechsleri (Korea and the United States) and P. nicotianae (United States, Korea, Brazil, Puerto Rico, Japan) have been known to be poinsettia pathogens for some time (Farr and Rossman 2015;Kanto et al 2007;Estevez de Jensen et al 2006). In Taiwan, P. cryptogea as well as P. nicotianae occurred on rotted poinsettia roots (Ann 1992), and Orlikowski also described P. cryptogea on poinsettia in Poland (Orlikowski and Ptaszek 2013). Some additional species have been seen on Euphorbia relatives of poinsettia, including P. cactorum, P. citricola, and P. palmivora.…”
Section: Geographic Occurrence and Impactmentioning
confidence: 99%
“…In Poland, the discussed species was first reported in the early 1970's in plantings of gerbera (Gerbera jamesonii) [Orlikowski 1976/77]. In the following years, the pathogen was isolated from pot plants, including cineraria (Senecio cruentus), Pachypodium lamerei [Orlikowski 1993], and poinsettia (Euphorbia pulcherrima) [Orlikowski and Ptaszek 2013], and from foil tunnel cultivations of Peruvian lilly (Alstroemeria × hybrida) [Ptaszek and Skrzypczak 2008]. Until now, P. cryptogea has also been recorded in container ornamental plant nurseries, in cultivation of both deciduous and coniferous plants [Orlikowski and Szkuta 2008, Orlikowski et al 2012a.…”
Section: Introductionmentioning
confidence: 99%